Y+9÷2=y-3÷4-(y/3)pls help
2 answers:
Step-by-step explanation:
There are 2 scenarios below. One without parenthesis and the second with. I believe the second one is your question.
- y+9÷2=y-3÷4-(y/3)
- y - y + y/3 = - 3/4 - 9/2 ⇒ combining like terms
- y/3 = -3/4 - 18/4
- y/3 = -21/4
- y = -21/4*3
- y = -63/4
- y = - 15 3/4
===============
- (y+9)÷2=(y-3)÷4-(y/3)
- 12*(y+9)/2 = 12* (y-3)/4 - 12*y/3 ⇒ this is to get rid of fraction
- 6(y+9) = 3(y-3) - 4y
- 6y + 54 = 3y - 9 - 4y
- 6y + 54 = - y - 9
- 6y + y = - 9 - 54
- 7y = - 63
- 7y/7 = -63/7
- y = -9
You might be interested in
Answer:
11
Step-by-step explanation:
Answer:
32
Step-by-step explanation:
Answer:
We need some aditional data. For example, the average number of students who like to snorkel in certain population.
Step-by-step explanation:
your answer would be (2,3)